Design of micro resistance measurement system. Issue 1 (January 2021) - Li, Qingrun; Wang, Shudong; Chen, Yun; Wang, Hao; Liu, Shen
Abstract: With the continuous progress and development of the electronics industry, the number and types of electronic components are also increasing. As the most widely used device in electronic components, the accuracy of resistors greatly affects the performance of the product. Therefore, we need to design a highly accurate and intelligent micro-resistance measurement system to meet the needs of the current society. This paper designs a micro-resistance measurement system. The system uses ST89C52 single-chip microcomputer as the data processing and control chip, and uses a constant voltage source to provide a stable voltage for the resistance to be measured. The measurement module of this system is based on the RC oscillator circuit, the pulse time is measured by the pulse counting method and then the measured frequency is calculated, because the frequency is a digital quantity that the single-chip microcomputer is relatively easy to identify and process; the selection module is mainly controlled by the 51 single-chip microcomputer. The gears correspond to different non-polar capacitors; LCD1602 displays the value and unit of the measured resistance. And the system uses the C language for software design, at the same time design the corresponding flow chart and write the complete source code for programming; finally, the corresponding physical objects are produced and corresponding debugging is carried out, and the debugging results meet the design requirements of the subject. By comparison, the general measurement methods have the disadvantages of complex calculations, and it is not easy to realize automatic measurement and intelligent. It has been verified that the system adopts these modules to make the test instrument more accurate and intelligent to achieve the required requirements.